2004
DOI: 10.1002/cbic.200300569
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterisation of an Artificial DNA‐Binding Cytochrome

Abstract: We aim to design novel proteins that link specific biochemical binding events, such as DNA recognition, with electron transfer functionality. We want these proteins to form the basis of new molecules that can be used for templated assembly of conducting cofactors or for thermodynamically linking DNA binding with cofactor chemistry for nanodevice applications. The first examples of our new proteins recruit the DNA-binding basic helix region of the leucine zipper protein GCN4. This basic helix region was attache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…It has been observed that the presence of only one BHR region attached to either the N or C terminus of the intact cyt b 562 does not promote tight, specific DNA binding. [20] However, the increase in helical content of the fragments in the presence of DNA (Supporting Information) suggests that both the bhrN12 and 34Cbhr fragments bind to DNA alone. This crucial difference should allow DNA to direct the assembly and so influence heme binding.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…It has been observed that the presence of only one BHR region attached to either the N or C terminus of the intact cyt b 562 does not promote tight, specific DNA binding. [20] However, the increase in helical content of the fragments in the presence of DNA (Supporting Information) suggests that both the bhrN12 and 34Cbhr fragments bind to DNA alone. This crucial difference should allow DNA to direct the assembly and so influence heme binding.…”
mentioning
confidence: 96%
“…Titration of bhrN12 and 34Cbhr with ferric heme (2 mm) revealed a low affinity for the cofactor (Figure 2 a); K D > 27000 nm AE 3000 is at least 1000-fold higher than that observed for the intact DBC. [20] Under reducing conditions, the bhrN12 and 34Cbhr fragments bind heme with an affinity (K D = 435 nm AE 85 nm) much lower than that of the oxidized form (Figure 2 b). In both oxidation states, the spectrum was identical to that of wild-type cyt b 562 , and the DBC was observed on the addition of 5 equivalents of bhrN12 and 34Cbhr (relative to heme), indicating that the helical bundle had assembled correctly (Supporting Information).…”
mentioning
confidence: 98%
See 3 more Smart Citations